Serum C-Reactive Protein and Congestive Heart Failure as Significant Predictors of Herpes Zoster Vaccine Response in Elderly Nursing Home Residents. (31st May 2017) - Verschoor, Chris P; Lelic, Alina; Parsons, Robin; Evelegh, Carole; Bramson, Jonathan L; Johnstone, Jennie; Loeb, Mark B; Bowdish, Dawn M E
Summary: The immunogenicity of the varicella-zoster virus vaccine in elderly nursing home residents has an inverse relationship with serum levels of C-reactive protein and heart failure status. Furthermore, heart failure in this population is associated with markers of T-cell immunosenescence. Abstract: Background: Elderly long-term care residents often exhibit a myriad of risk factors for immune dysfunction, including chronic inflammation and multiple comorbid conditions, which undoubtedly contribute to their enhanced susceptibility to infection. Hence, understanding the factors required for optimal vaccine responsiveness is critical. Methods: We examined 187 elderly nursing home residents (aged 80–102 years) and 50 community-dwelling seniors (aged 60–75 years) immunized with the live-attenuated varicella-zoster virus (VZV) vaccine. Specifically, we examined whether vaccine responsiveness was associated with serum C-reactive protein (CRP), tumor necrosis factor, interleukin 1β, 6, and 10, leukocyte telomere length, chronic disease status, and frailty. Results: Elderly participants had significantly higher levels of CRP, tumor necrosis factor, and interleukin 6 and shorter leukocyte telomere length. Vaccine responsiveness was inversely related to the CRP level in elderly participants, but not seniors, and those with congestive heart failure were less likely to achieve a 2-fold response (odds ratio, 0.08). The latter relationship is probably due to immunosenescence, because heart failure was associated with increased senescent CD4 + T cells, and reduced naive and effector and central memory CD8 + T cells. Conclusions: In summary, these data improve our understanding of vaccine responsiveness for those in long-term care, suggesting that certain risk factors are associated with a greater likelihood of vaccine failure.